Team Member Performance at the One-Stop Integrated Administration System: Motivation, Discipline, and Leadership - Rahmat Rahmat; Ahmad Juwaini; Azis Firdaus (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines the influence of work motivation, work discipline, and leadership on team member performance at the Bogor Regency SAMSAT Office. A quantitative causal-associative approach was employed using a census of 102 employees. Data were collected through questionnaires, observations, and interviews, and analyzed using SPSS version 27 through correlation and multiple regression analysis. The findings reveal that work motivation, work discipline, and leadership positively and significantly affect team member performance, both partially and simultaneously. Work discipline was identified as the most dominant factor influencing performance. The regression model explains 51.9% of the variance in team member performance. These findings imply that improving employee performance in public sector organizations requires stronger discipline systems supported by effective leadership and sustained motivation. Future studies are recommended to include additional variables and broader institutional contexts.